Caracterização de parâmetros e ignição térmica de onda de choque em tubo de choque usando simulação numérica - Claudio Marcio Santana (2018)
The present work consisted in developing a computational routine to predict and characterize the parameters of ignition delay time, shock wave pressure, chemical reaction velocity, shock wave propagation velocity, Mach number, flame temperature, density of the products generated in the combustion and energy released in the combustion process of the shock wave in a shock tube. Mathematical modeling considered the high-pressure region of the shock tube known as the conducted section. The Lazarus code compiler was used to generate unstructured triangular meshes and implementation of computational routines to simulate the propagation of shock waves inside the shock tube. The mathematical modeling used the geometric parameters of the shock tube of the combustion laboratory of the Federal University of Minas Gerais and was based only on the displacement of the shock wave after rupture of the diaphragm. Results of the experimental tests carried out by Santana (2013) on ethanol, diesel and biodiesel were compared and correlated with work done by other authors to generate input data for simulation. These data were used to simulate the behavior of the shock wave in the shock tube. The main objective of this work was the development of computational routines to characterize the shock wave parameters without and with combustion, to validate the experimental tests performed in the combustion tube of the combustion laboratory of the Federal University of Minas Gerais conducted by Santana (2013). Valente (2016) and Guimaraes (2016). The results obtained in the simulation were confronted with experimental tests and were considered satisfactory, since they are in the same order of magnitude of the results found in the experimental tests performed in the shock tube by Santana (2013) and other works. It can be stated that it is possible to carry out measurements of ignition delay times of fuels using shock tube from the combustion laboratory of the Federal University of Minas Gerais.